The Effect Of Peanuts Aquafaba (Arachis Hypogaea L) On The Sensory And Physical Quality Of Lidah Kucing Cookies - Shasa Keishya; Guspri Devi Artanti; Annis Kandriasari (Community Engagement and Emergence Journal (CEEJ), 2026)
This study aimed to investigate the effect of using peanuts aquafaba on the sensory and physical quality of ‘lidah kucing’ cookies. A quantitative experimental design was employed, with three treatment groups varying the ratio of water to peanut aquafaba: 1:2, 1:3 and 1:4. Sensory quality was assessed by semi-trained panellists in terms of colour, scent, crispness, sweetness, peanuts flavour and aftertaste using the Kruskal-Wallis test followed by Tukey’s test, whilst physical quality was analysed using ANOVA with a completely randomised design followed by Duncan’s test. The results of the study showed that peanuts aquafaba had no effect on the colour, scent, crispness, and sweetness of ‘lidah kucing’. However, there was an effect on the peanut flavour and peanut aftertaste, with the 1:2 treatment yielding the highest scores due to the higher concentration of aquafaba. In terms of physical quality, the 1:2 treatment produced the highest baking loss (39.2%) and was deemed the best as it indicated optimal water evaporation, whilst in terms of spreading power, the 1:4 treatment produced the highest spreading power (126.9%); consequently, the 1:2 treatment (68.1%) was assessed as the best treatment due to its low spreading power, resulting in a more stable and firm cake shape during the baking process. Peanuts aquafaba has the potential to serve as a plant-based alternative to egg white in ‘lidah kucing’ cookies, with optimal characteristics varying according to the concentration used.